Regional Economic Outlook, April 2012, Sub-Saharan Africa : Sustaining Growth amid Global Uncertainty. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2012)
Sub-Saharan Africa continues to record strong economic growth, despite the weaker global economic environment. Regional output rose by 5 percent in 2011, with growth set to increase slightly in 2012, helped by still-strong commodity prices, new resource exploitation, and the improved domestic conditions that have underpinned several years of solid trend growth in the region's low-income countries. But there is variation in performance across the region, with output in middle-income countries tracking more closely the global slowdown and with some sub-regions adversely affected, at least temporarily, by drought. Threats to the outlook include the risk of intensified financial stresses in the euro area spilling over into a further slowing of the global economy and the possibility of an oil price surge triggered by rising geopolitical tensions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet